What does quality of care mean for maternal health providers from two vulnerable states of India? Case study of Bihar and Jharkhand. Issue 1 (December 2016) - Karvande, Shilpa; Sonawane, Devendra; Chavan, Sandeep; Mistry, Nerges
Abstract Background Quality instillation has its own challenges, facilitators and barriers in various settings. This paper focuses on exploration of quality components related to practices, health system challenges and quality enablers from providers' perspectives with a focus on maternal health studied through a pilot research conducted in 2012–2013 in two states of India—Bihar and Jharkhand—with relatively poor indicators for maternal health. Methods Qualitative data through in-depth interviews of 49 health providers purposively selected from various cadres of public health system in two districts each from Bihar and Jharkhand states was thematically analysed using MAXQDA Version 10. Results Maternity management guidelines developed by the National Health Mission, India, were considered as a tool to learn instillation of quality in provision of health services in various selected health facilities. Infrastructure, human resources, equipments and materials, drugs, training capacity and health information systems were described as health system challenges by medical and paramedical health providers. On a positive note, the study findings simultaneously identified quality enablers such as appreciation of public-private partnerships, availability of clinical guidelines in the form of wall posters in health facilities, efforts to translate knowledge and evidence through practice and enthusiasm towards value of guidelines. Conclusions Against the backdrop of quality initiatives in the country to foster United Health Care (UHC), frontline health providers' perspectives about quality and safety need to be considered and utilized. The provision of adequate health infrastructure, strong health management information system, introduction of evidence-based education and training with supportive supervision must constitute parallel efforts.